Predictive Assessment of Cancer Center Catchment Area from Electronic Health Records - Salmasi, Luca; Capobianco, Enrico (Frontiers in Public Health, 2017)
Healthcare facilities may identify catchment areas (CA) by selecting criteria that depend on a variety of factors. These refer to hospital activities, geographical definition, patient covariates, and more. The analyses which were traditionally pursued have a limiting factor in the consideration of only static conditions. Instead, some of the CA determinants involve influences occurring at both temporal and spatial scales. The study of CA in the cancer context means choosing between healthcare facilities, usually divided into general hospitals versus oncological centers. In the CA context, Electronic Health Records (EHR) promise to be a valuable source of information, one driving the next generation patient-driven clinical decision support systems. Among the challenges, Digital Health requires the re-definition of a role of stochastic modelling to deal with emerging complexities from data heterogeneity. To model CA with cancer EHR, we have chosen a computational framework centered on a logistic model, as a reference, and on a multivariate statistical approach. We also provided a battery of tests for CA assessment. Our results indicate that a more refined CA model’s structure yields superior discrimination power between health facilities. The increased significance was also visualized by comparative evaluations with ad hoc geo-localized maps. Notably, a cancer-specific spatial effect can be noticed, especially for breast cancer and through oncological centers. To mitigate the data distributional influences, bootstrap analysis was performed, and gains in some cancer-specific and spatially concentrated regions were obtained. Finally, when the temporal dynamics are assessed along a 3-year timeframe, negligible differential effects appear between predicted probabilities observed between standard critical values and bootstrapped values. In conclusion, for interpreting CA in terms of both spatial and temporal dynamics, sophisticated models are required. The one here proposed suggests that bootstrap can improve test accuracy. We recommend that evidences from stochastic modelling are merged with visual analytics, as this combination may be exploited by policy makers in support to quantitative CA assessment.